STUDI KETERSEDIAAN HAYATI ABSOLUT DAN BIODISTRIBUSI KURKUMIN NANOPARTIKEL PADA HEWAN PERCOBAAN - Trias Pradana, Aditya
Curcumin is an diarylheptanoid organic compound, by aromatic polyketides biosynthetic pathways from the rhizome of Curcuma genus. Curcumin exhibits poor solubility and low bioavailability as an oral drug. Curcumin nanocystal was produced in the previous study by high pressure homogenation and pearl milling method to enhance solubility and peroral absorbtion. The aim of this study is to characterize nanocurcumin product, compare the absolute bioavailability and study its biodistribution in animal. Characterization of nanocurcumin was performed including size and polydispersity index, zeta potential, macroscopic, microscopic, morphology observation with Scanning Electron Microscopy (SEM), characteristic of crystal with X-ray Diffraction (XRD) and thermal analysis with Differential Scanning Calorimetry (DSC). Absolute bioavailability were tested in Wistar rat. Curcumin and nanocurcumin were given through oral and intravenous route with dose of 10 mg/kg bw. Sampling time was 0; 0,25; 0,5; 1; 2; 4; 8; 12 and 24 hour after administration. Biodistribution was tested using radioiodine labeling method to determine the accumulation of curcumin in distribution phase. Part of tissues were taken and radioactivity was counted. Nanocurcumin has average size 478 nm, polydispertion index 0.442 and zeta potential -23.68 mV. Physical characteristic of nanocurcumin (size and morphology) is better than curcumin. Nanocurcumin improved absolute bioavailability of curcumin as seven-fold. At distribution phase, curcumin was accumulated in liver, stomach and intestine based on its rapid metabolism by enzymatic process.